Effects of therapeutic plasma exchange (TPE) on efficacy and adverse events in patients with autoimmune neurological diseases: a systematic review and meta-analysis based on real-world studies and single-arm clinical trials - Jinyu Tao; Xiaoqin Yang; Han Tang; Jialin He; Siyin Gong; Jinfang Li (Frontiers in Neurology, 2026)
Background Therapeutic plasma exchange (TPE) is a core intervention for autoimmune neurological diseases (ANDs). To date, clinical efficacy and safety of TPE across disease subtypes, age strata and regions have not been systematically synthesized. This meta-analysis aimed to evaluate the clinical response, mortality and adverse event (AE) rates of TPE in patients with ANDs. Methods Relevant real-world observational studies and single-arm trials were retrieved from PubMed, Embase and Cochrane Library. We conducted single-arm meta-analysis to pool effect sizes with 95% confidence intervals (CIs). Subgroup and leave-one-out sensitivity analyses were used to assess heterogeneity and result stability. Results In total, 38 studies comprising 2,199 patients were included. Response rates differed significantly across study-level age strata, whereas differences across disease and regional subgroups were not statistically significant. The all-cause in-hospital mortality rate among patients undergoing TPE was 4% (95% CI: 3–5%, I 2 = 36.5%), and this value does not represent mortality attributable to TPE. A total of 49 fatal cases were reported. The most common adverse events were hypotension (12%), coagulation disorders (11%), catheter-related infections (8%), allergic reactions (7%), and hypocalcemia (7%). Some studies reported adverse events as per the number of patients and others as per TPE sessions. This study calculated the incidence rates of adverse events based on the number of patients. Conclusion Patients with ANDs show a relatively high rate of clinical improvement after TPE. Most deaths are attributable to underlying disease progression rather than TPE itself. Further high-quality multicenter studies are required to optimize patient selection and treatment protocols for TPE.